Pengaruh Model Pembelajaran Project Based Learning Terhadap Kemampuan Berpikir Kritis dan Kreativitas Pada Mata Pelajaran Biologi di SMAN 4 Palu - Aisyah; Jamhari, Mohammad; Buntu, Amalia; Rafiqa; Laenggeng , Abd. Hakim; Zainal, Syech (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the effect of the Project Based Learning learning model on critical thinking skills and creativity in biology subjects at SMA Negeri 4 Palu. This type of research is quantitative with a quasi-experimental type. The population in this study was 400 people and the sample in this study was 70 people. Sampling was done by purposive sampling, and the research sample was 2 classes consisting of class XC and XJ. The data collection technique in this study was using a test in the form of a Post-test and observation sheet. Data analysis used prerequisite tests, namely, normality tests and homogeneity tests and hypothesis testing using independent sample-t tests. The results of the study indicate that (1) students' critical thinking skills had a significant average score in class XJ as the experimental class, namely 85.66, and class XD as the control class, namely 77.14. (2) The results of observing students' creativity in the experimental class yielded a score of 84.66, with 80-100% falling into the “very creative” category, while the control class scored 76.14, with 61-80% falling into the “creative” category. (3) The Project-Based Learning (PBL) model has a significant impact on critical thinking skills and creativity in biology lessons at SMA Negeri 4 Palu. This is evidenced by the t-test results, which show a significance value of 0.00 < 0.05.